2019
DOI: 10.1155/2019/1486476
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Myeloid and Lymphoid Neoplasms: A Single-Center Experience

Abstract: The coexistence of a myeloid and a lymphoid neoplasm in the same patient is a rare finding. We retrospectively searched the records of the Hematology Division of the Second Department of Internal Medicine and Research Institute at Attikon University General Hospital of Athens from 2003 to 2018. Nine cases have been identified in a total of 244 BCR-/ABL1- negative MPN and 25 MDS/MPN patients and 1062 LPD patients referred to our institution between 2003 and 2018. Each case is distinct in the diversity of myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Biologically, it has been speculated that the co-occurrence of myeloid and lymphoid neoplasms may be sustained by a common clonal progenitor ( 13 , 14 ). This could be assumed particularly in MPN patients with a demonstrated driver mutation, preceding LPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, it has been speculated that the co-occurrence of myeloid and lymphoid neoplasms may be sustained by a common clonal progenitor ( 13 , 14 ). This could be assumed particularly in MPN patients with a demonstrated driver mutation, preceding LPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up treatment, 35% of patients died due to the progression of LPDs (two patients), heart failure (one patient), renal failure (one patient) and COVID-19 (one patient). 3 1 MM 7 + PMF 5 2 CLL 6 /PV 3 1 atypical CLL 6 (score 3)/PMF 5 5 PV 3 + CLL 6 2 PMF 5 + CLL 6 1 ET 8 + CLL 6 1 PMF 5 + MM 7 1 ET 8 + MM 7 1 PV 3 + MM 7 1 PMF 5 + NHL DLBCL 4 1 PV 3 + NHL DLBCL 4 1 PV 3…”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of two distinct hematology neoplasms in the same patient is very rare; therefore, little is known in regard to the clinical characteristics, thrombotic complications and survival chances of this scenario. Considered etiopathogenetic mechanisms, some genetic abnormalities ( JAK2V617F , BCR/ABL1 , PDGFRA , PDGFRB , TET2 , SF3B1 ) were described which can lead to either myeloid or lymphoid malignancies [ 6 , 7 , 8 ]. A Swedish registry study revealed a 5- to 7-fold elevated risk of MPNs and a 1.6-fold increased risk of CLL among first-degree relatives of MPN patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of lymphoma and MF in the same patient is a relatively uncommon event, described mostly sporadically in case reports. Biologically, it has been speculated that the co-occurrence of myeloproliferative neoplasms (MPNs) lymphoma may be sustained by abnormal cloning and genetic changes of early hematopoietic progenitor cells [6,7]. A report by Rumi et al described that the increased risk of lymphoproliferative neoplasms (LPN) in MPN Am J Transl Res 2024;16(3):730-737 patients may be multi-factorial, including genetic susceptibility (i.e., p53, VHL, SNPs), acquired mutations (JAK2V617F), and impaired immune monitoring [8,9].…”
Section: Potential Associationmentioning
confidence: 99%